Infrared study of high-pressure molecular phases of carbon dioxide: Cryocrystals - Giordano, Valentina M.; Gorelli, Federico A.; Bini, Roberto (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The infrared absorption spectra of the high-pressure crystalline phases II, III and IV of solid CO2 were studied by using a resistive heated diamond anvil cell up to 30 GPa. The employment of crystal slabs having thickness of ~ 2 mm allowed the study of the strongly absorbing fundamental bending and antisymmetric stretching modes without saturation. These are the first data for phases II and IV in the fundamental modes spectral region, furthermore the high samples quality allowed to improve, with respect to previous studies, the characterization of the infrared spectra of phases I and III. The comparison of the spectral structure and of the frequency evolution with pressure of the crystal modes between phase I and the higher pressure phases clearly indicates the close resemblance among all these phases. In particular, the dramatic change of the intermolecular interaction claimed for phases II (dimeric association) and IV (large molecular bending) can be ruled out and, as a consequence, the hypothesis of a transition from the molecular phase I to the silica-like phase V through intermediate nonmolecular phases discarded.